Valoración comercialdel excedente de la producción de Orito en el Cantón La Maná - Masapanta Masapanta, Martha Edelina (2017)
The research project was developed with the purpose of designing a proposal for assessing the excess of production of bananas in La Mana town, allowing to search a new alternative for the sale of the product, especially to give solution to the problem explained before, which causes losses to the producers because the fruit stays on farms and it is not being used. The research was carried out on the field and uses bibliography because it was necessary to collect information for the research and it was applied on the commercial area of the production of bananas in La Maná town. As research methods we applied the deductive, inductive and analytical method which allowed us to identify the problems that arise at the time of marketing the bananas. The project techniques that were used were the interview which was applied to the legal representatives of the companies of bananas, the survey addressed to producers of bananas in the La Maná and a census focused on managers of distribution of bananas. The results obtained with its application, is in 377 bananas producers which annually generates a surplus of fruit of 1’803.360 clusters to be processed reaches 901.680 boxes, another result is the sale of bananas to the two exactions in La Maná as an alternative, for which same strategies were made viable the sale of this fruit. The development of this model is for the benefit of the producers of bananas “orito” in La Maná.